Motives and accountants’ role for green accounting-reporting towards minimizing financial leakages / Haslinda Yusoff … [et al.] - Yusoff, Haslinda; Othman, Radiah; Ismail, Allezawati; Darus, Faizah (Universiti Teknologi MARA Cawangan Selangor, 2016)
The accounting and reporting practices on Malaysian business environmentally related matters are generally low and descriptive in form. The prevailing literature indicates that the motives behind green accounting and reporting (GAR) practices are primarily market-based. Thus, it is crucial to understand the reasons behind the low practices despite various supports from the government, regulatory bodies, professional bodies and others. At the individual level, the accountants can play a very significant role in pushing for GAR in their organizations. This study surveyed the current role of accountants pertaining to GAR using the survey method. mail and online questionnaires were sent to accountants and the survey responses were analysed using factor and regression analyses. Three key motivating factors emerged from the factor analysis, namely; (1) shareholders’ value (2) stakeholder engagement and regulatory pressure and (3) highly related to stakeholder engagement. The factor analysis also revealed two types of accountants’ role pertaining to (GAR), namely; (1) a mix of proactive, defensive and reactive (2) accommodative. The only significant organizational characteristics found to be statistically related to the motivating factors for GAR is the type of organization.